Letter to the Editor concerning “Impact of preoperative mental health disorders on postoperative outcomes in patients with adolescent idiopathic scoliosis undergoing surgery” by Vallee EK, et al. (Spine Deformity [2026]: doi:10.1007/s43390-026–01288-z) - Kishankumar Mahida; Snehal Rajendra Jagtap (Spine Deformity, 2026)
PURPOSE: To identify and classify free mobile applications for adult cancer patient education available in the App Store and Google Play. METHODS: A technology foresight study was conducted in four phases (preparation, pre-prospecting, prospecting, and post-prospecting). Search was carried out in both stores, using the terms "cancer" and "oncology". Free apps in English, Spanish, or Portuguese aimed at educating adults with cancer were included. Quality was assessed based on a scale adapted from the Applications Scoring System. RESULTS: A total of 848 apps were identified. After screening, 32 met the inclusion criteria. Most were categorized under "Medicine" (n = 21), were available in the App Store (n = 25), and were released between 2017 and 2024, peaking in 2024 (n = 14). Content most frequently addressed breast cancer. Only nine apps achieved the maximum app comprehensiveness score, and seven cited scientific literature. Most required internet connectivity (n = 28) and were easy to navigate (n = 29), whereas professional validation and offline resources were limited. Overall quality scores ranged from 5 to 10, with a median score of 8 (interquartile range [IQR]: 6-9). CONCLUSION: Although digital solutions for oncology education have expanded rapidly, a substantial proportion of available applications remain devoid of a rigorous scientific foundation and continue to exhibit significant barriers to digital accessibility. The development and dissemination of inclusive, evidence-based, and clinically validated digital tools are therefore essential to ensure their effectiveness, reliability, and equitable adoption in oncology education.